Do Energy Efficiency and Technology Boost Sustainable Environment: Evidence from GCC Countries - Elhaj, Manal (Journal of Ecohumanism, 2024)
Sustainable Environment practices significantly reduce carbon emissions by ensuring the continuous use of materials and energy resources, thus making them intrinsically aligned with the underlying objectives of the decarbonization agenda. Technological advancement has the potential to contribute significantly to this shift by streamlining resource flows, enhancing waste management procedures, and allowing more efficient energy consumption. Although Gulf Cooperation Council countries have experienced robust economic growth over the decades, rising pollution emissions and low renewable energy consumption have raised concerns among policymakers about the long-term stability of this growth. In recent years, Gulf countries have paid significant concern to environmental matters and achieved carbon-free development. This study seeks to investigate the relationship between energy efficiency, technology, and sustainability, particularly emphasizing the green economy perspective. Carbon dioxide emission taken as the dependent variable. Frontier Technology Readiness Index reflects the utilization of technology within economies. Energy efficiency is also considered, symbolizing the transition from fossil fuels to green energy due to technological progression in the energy sector. The findings suggest that factors such as the Frontier Technology Readiness Index, the energy intensity level of primary energy, and medium and high-tech manufacturing significantly harm the environment, while scientific and technical journal articles and agriculture significantly improve the environment over time. To improve Gulf Cooperation Council countries’ environmental quality, policymakers must understand the factors causing climate change. This study gives policymakers useful information about how to make the Gulf Cooperation Council community more sustainable by looking at energy efficiency, technology, and digital adaptation.